In Situ Observations of Ice Particle Losses in a Young Persistent Contrail. Issue 24 (28th December 2018) - Kleine, J.; Voigt, C.; Sauer, D.; Schlager, H.; Scheibe, M.; Jurkat‐Witschas, T.; Kaufmann, S.; Kärcher, B.; Anderson, B. E.
Abstract: We describe results of in situ observations of a 1‐ to 2‐min‐old contrail in the vortex phase generated from soot‐rich exhaust (>10 15 emitted soot particles per kilogram of fuel burned). Simultaneous measurements of soot (EIsoot ) and apparent ice (AEIice ) particle number emission indices show a pronounced anticorrelation in the vertical contrail profile. AEIice decrease by about 75% with increasing distance below the contrail‐producing aircraft, while EIsoot increase by an equivalent relative fraction, therefore strongly suggesting ice particle formation to be soot‐controlled and losses to be caused by sublimation. Quantifying these losses in measurements helps to validate and improve contrail parameterizations used to estimate the climate impact of contrails and contrail cirrus. Our study further demonstrates the challenges in the performance and interpretation of particle measurements in young contrails and lends itself to suggestions for improving contrail data evaluation. Plain Language Summary: Detailed understanding of climatic effects of aircraft contrails and the clouds evolving from them requires accurate in situ measurements. We took measurements in a young persistent contrail that formed at 10 km altitude. We found that a substantial fraction of contrail ice particles is lost shortly after they formed from emissions of copious soot particles from aircraft jet engines. While these results are not entirely unexpected and can be explained by sublimation associated with adiabatic heating in descending aircraft wake vortices, experimental verification is challenging. Importantly, our results increase confidence in the current understanding of processes governing contrail ice formation, growth, and sublimation during early development stages. We provide guidance on quantifying ice particle number concentrations in young contrails and how to relate them to particle emissions. We expect our results to be also beneficial to future studies addressing properties and climate impact of contrails originating from using alternative jet fuels or novel engine technologies. Key Points: Results of aircraft measurements of microphysical properties in a young, soot-rich contrail are presented We found a pronounced reduction of ice particle numbers in lower wake regions Vertical profiles of soot and ice particle numbers are consistent with soot-controlled ice formation